Język gaelicki – historia, przyczyny upadku i szanse przetrwania - Stalmaszczyk, Piotr (Acta Universitatis Lodziensis. Folia Linguistica, 1992)
The paper discusses the history and fate of Scottish Gaelic since its arrival in Scotland in the 5th century. Once the most important language of Scotland, Gaelic undergoes now sociolinguistic changes indicating the process known as language death. Some of the causes of decline include the loss of status, lack of literature and education in Gaelic, territorial and social disunity, massive emigration, and the overwhelming influence and impact of the English language. Unless institutional and individual attitudes towards the language change, the next century may witness the death of yet another Celtic tongue.